2021
DOI: 10.1177/03000605211014375
|View full text |Cite
|
Sign up to set email alerts
|

Association between functional mitral regurgitation and recurrence of paroxysmal atrial fibrillation following catheter ablation: a prospective cohort study

Abstract: Objective The present study aimed to investigate the effect of functional mitral regurgitation (FMR) on recurrence of paroxysmal atrial fibrillation (PAF) in patients undergoing radiofrequency catheter ablation. Methods This prospective cohort study comprised 107 patients with PAF. The patients were divided into the FMR and non-FMR groups. FMR was assessed by Doppler echocardiography before index ablation. All patients initially underwent circumferential pulmonary vein isolation (CPVI) and were followed up for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
2
2
Order By: Relevance
“…[31] On the contrary, in a smaller-scale study, MR was not found to be an independent determinant of post-ablation AF recurrence in patients undergoing catheter ablation for PAF. [32] In our study, similarly, higher degrees of MR were observed in the group experiencing recurrence, but it was not identified as an independent variable in Cox regression analysis. This finding is consistent with the study conducted by Ke et al, [32] which initially appeared to have similar high MR degrees.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…[31] On the contrary, in a smaller-scale study, MR was not found to be an independent determinant of post-ablation AF recurrence in patients undergoing catheter ablation for PAF. [32] In our study, similarly, higher degrees of MR were observed in the group experiencing recurrence, but it was not identified as an independent variable in Cox regression analysis. This finding is consistent with the study conducted by Ke et al, [32] which initially appeared to have similar high MR degrees.…”
Section: Discussioncontrasting
confidence: 46%
“…[32] In our study, similarly, higher degrees of MR were observed in the group experiencing recurrence, but it was not identified as an independent variable in Cox regression analysis. This finding is consistent with the study conducted by Ke et al, [32] which initially appeared to have similar high MR degrees.…”
Section: Discussioncontrasting
confidence: 46%
“…[15] Conflicting data on the association between functional MR and the risk of AF recurrence post-ablation were reported in these 2 studies. Furthermore, both of these studies included patients who mainly had mild functional MR, and only 5% (2/40) [14] and 9% (6/66) [15] of patients had significant functional MR.…”
Section: Discussionmentioning
confidence: 99%
“…[14] In contrast, a recent study conducted by Ke and colleagues showed that functional MR was not an independent risk factor for predicting the recurrence of catheter ablation for paroxysmal AF. [15] Conflicting data on the association between functional MR and the risk of AF recurrence post-ablation were reported in these 2 studies. Furthermore, both of these studies included patients who mainly had mild functional MR, and Patients with significant functional MR had a higher rate of recurrence of atrial tachyarrhythmia than those without significant functional MR (42.9% vs 15.1%, P < .001 by the log-rank test).…”
Section: Discussionmentioning
confidence: 99%